2017
DOI: 10.3390/en10101505
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Potential for Use of Floating PV Power Plant on the Skadar Lake for Electricity Supply of Aluminium Plant in Montenegro

Abstract: This paper deals with a conceptual solution for the supply of a part of electrical energy for the needs of Aluminium Plant Podgorica (KAP) in Montenegro from a large Floating Photovoltaic Power Plant (FPPP), that would be installed on the nearby lake. The recommended FPPP, with an innovative azimuth angle control method and total installed power of 90 MWp, would consist of 18 power plants having an installed power of 5 MWp each. An analysis using the NREL solar insolation database ascertained that the recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 23 publications
0
23
0
4
Order By: Relevance
“…Therefore, if the effect of the water bodies on the air temperature in the photovoltaic system is known [63,85,89], this study opens new scenarios about the effects of the presence of vegetation between and around the photovoltaic panels. However, it should be noted that for the sake of simplification, the analysis has been carried out without considering the presence of panels and their arrangement difference between the simulations, which is left to future evaluations.…”
Section: Boundary Conditions Cyclicmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, if the effect of the water bodies on the air temperature in the photovoltaic system is known [63,85,89], this study opens new scenarios about the effects of the presence of vegetation between and around the photovoltaic panels. However, it should be noted that for the sake of simplification, the analysis has been carried out without considering the presence of panels and their arrangement difference between the simulations, which is left to future evaluations.…”
Section: Boundary Conditions Cyclicmentioning
confidence: 98%
“…Their environmental impact, energy consumption and management costs are significantly reduced compared to other purification systems [82][83][84]. From an economic point of view, the positioning of the panels in the artificial basin allows the increase of energy produced compared to the ground photovoltaic system because the photovoltaic panels can exploit the solar radiation reflected by the water's surface (albedo) [63,[85][86][87][88][89]. Furthermore, the presence of water and vegetation reduces the panels' overheating, which is one of the main causes of efficiency loss of GPV systems, and improves their ecological and cultural value [56,[88][89][90].…”
Section: Step 2 Identification Of the Priority Ecosystem Services Anmentioning
confidence: 99%
“…Fortunately, energy harvesting technologies for lake applications are in development, which have the potential to benefit Lake Atitlan if invested in when available. Examples of these are sediment microbial fuel cells tested in Taihu Lake, China, a process of generating electricity from carbohydrate and protein-rich cyanobacteria [65]; a technology added to a wastewater treatment plant to treat dissolved organic matter from raw lake water while simultaneously generating electricity using a microbial fuel cell [66]; or thirdly, a study in Skadar Lake, Montenegro, testing the potential use of floating photovoltaic cells for renewable electricity supply [67]. Another promising renewable energy in the basin is geothermal energy, a resource yet to be exploited, and the Atitlan basin is indicated as an area of interest for investment in the renewable energy [68].…”
Section: Energy Security Challengesmentioning
confidence: 99%
“…Moreover, the application of explicit and implicit temperature correlations is not limited to performance assessment of PV systems only. The temperature correlations also facilitate performance evaluation of PV-Thermal (PVT), 26,27 building integrated PV (BIPV), 3,28 concentrated PV (CPV) 29 bifacial PV 30 and floating PV (FPV) systems 25,31 ; however, such installations are very less in comparison with ground installations for which these temperature correlations have been reported. For a BIPV system operational at a site in Thailand, Trinurku et al 3 compared the effectiveness of two correlations and found that the heat exchange between module and environment is greatly influenced by air gap and tilt angle between the rear surface of PV module and roof.…”
Section: Name Correlationmentioning
confidence: 99%